Typical Frankia infect actinorhizal plants exotic to New Zealand - Michael L. Clawson; David R. Benson; Steven C. Resch; David W. Stephens; Warwick B. Silvester (New Zealand Journal of Botany, 1997)
Frankia strains are actinomycetes that fix N 2 in root nodules of plants classified in eight families of the Angiospermae. The wide variety of plants infected has raised questions about the ecology and diversity of Frankia symbionts, and their co‐evolution with actinorhizal plants. Partial sequencing was done of the small subunit (16S) rRNA gene from Frankia endophytes present in the root nodules of Alnus cordata , A. glutinosa , A. viridis , Casuarina equisetifolia, Coriaria arborea, C. plumosa , and Elaeagnus pungens growing in New Zealand. With the exceptions of the Coriaria spp., all of the plants are exotic to New Zealand. Analysis of the 16S rRNA gene indicates that the exotic species were nodulated by Frankia strains that cluster with strain groups previously shown to be typical for each actinorhizal host. Frankia in 12 native Coriaria spp. nodules yielded two sequences differing in only one position, suggesting a relatively low diversity compared with the exotic species.